A review of waste management approaches to maximise sustainable value of waste from the oil and gas industry and potential for the State of Qatar. (15th January 2023) - Shahbaz, Muhammad; Rashid, Naim; Saleem, Junaid; Mackey, Hamish; McKay, Gordon; Al-Ansari, Tareq
Highlights: A critical review on type and point of generation of Oil and gas industry waste. Discussion on commercial and emerging treatment methods of produced water. Detailed analysis of oil sludge commercial and emerging treatment technologies. A comprehensive review on the treatment of flue gases and their possible utilisation. Potential for the oil and gas industry utilisation in Qatar. Abstract: Globally, the oil and gas industry produces a large volume of waste in the form of produced water, oil sludge, and flue gases that can pose a negative impact on environment. As such there is a need for the treatment and safe handling of this waste. Although, several techniques have been developed for the treatment of oil and gas industry waste, recent research trends have highlighted that for the sustainable treatment and management of oil and gas industry waste, it should be coupled with resource recovery and re-utilization concepts in line with circular economy perspectives. Essentially, converting waste into economic value added products, reducing environmental impacts and supporting sustainability within the oil and gas industry is of paramount importance. This study reviews basic three types of wastes streams, including solid waste (oil sludge), flue gases (CO2 and SO2 ), and liquids (produced water) originating from the oil and gas industry. The second aim is to review their characterization and respective treatment technologies, challenges, and possible emerging opportunities. An insight into the resource recovery and reuse potential for all three type of wastes considered is also provided. Finally, a case study from the State of Qatar is provided to assess the theoretical resource recovery and market/economic potential from selected wastes.